PENERAPAN EFEKTIVITAS RELAKSASI BENSON TERHADAP KUALITAS TIDUR PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) YANG MENJALANI HEMODIALISIS DI RSUD TARAKAN JAKARTA PUSAT - Dewi, Ratna; Irawati, Diana; Anggaraini, Dewi; Jumaiyah, Wati; Suryanti, Asih Dwi (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
Background: Hemodialysis patients can experience psychological problems such as: stress, anxiety, depression, and insomnia or disturbed sleep quality. Prolonged sleep quality disturbances can have an impact on the patient's quality of life, thus requiring interventions that are safe and easy to implement, one of which is Benson relaxation. The aim of applying Benson's relaxation to sleep quality in chronic kidney disease (CKD) patients undergoing hemodialysis. The application of evidence based nursing practice (EBNP) is through literature searches via the PubMed data base with the final result being an article entitled